THE INFLUENCE OF LEISURE TOURISM ON THE WELL-BEING OF CITIZENS OF UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this research psychological, social and economic effect of the contribution of leisure tourism among the concerned citizen well-being of Uzbekistan in analyzed. Through secondary research of academia and government sources of information including statistics on tourism, it is proven that tourism highly contributes in the reduction of stress and in the promotion of mental health. Tourism provides as economic support its supporting local economies by creating jobs, investing in infrastructure and enhancing living standards. This is good because in social terms it encourages cultural exposure, brings community pride and makes people involved with their culture of heritance. As tourists grow and exceed capacity, the research also highlights challenges, like cultural commercialization and intercommunity social tension, that may arise. This study highlights that issues of such importance as sustainable tourism practice are important for a positive influence on tourism and preservation of environment, as well as of culture. Our results reveal that the tourists not only gain, but the whole community also reaps the long-term benefits during the process of tourism development.